The assessment of a novel lower body resistance garment as a mechanism to increase the training stimulus during running: a randomised cross-over study - Samantha M. Hoffmann; Isaiah Di Domenico; Paul K. Collins (BMC, 2022)
Abstract Background This study examined the physiological and perceived impact of wearing a novel lower body resistance garment during exercise and recovery. Methods Using a randomised cross-over design, 15 recreationally-active males performed 2 × 10-min steady-state runs followed by a 10-min passive recovery with concomitant monitoring of oxygen consumption (V̇O2), heart rate (HR) and rating of perceived exertion (RPE; exercise portion only), wearing either the resistance garment (experimental) or running shorts (control). Results During exercise, there was a trend for V̇O2 and RPE to be higher (4.5% and 7.7% respectively) in experimental than control (V̇O2: r = 0.24, p > 0.05; RPE: r = 0.32, p > 0.05) and for HR to be lower (− 0.4%, r = − 0.05, p > 0.05). During recovery, V̇O2 and HR tended to be lower (4.7% and 4.3% respectively) in experimental than control (V̇O2: r = − 0.32, p > 0.05; HR: r = − 0.27, p > 0.05). Conclusions Though effects were trivial to small, and not statistically significant, these findings provide proof of concept and suggest that this garment design may increase the training stimulus during running and aid post-exercise recovery.